Enhanced fertility after diagnostic hysterosalpingography using water-soluble contrast media - Sedeq, Media Ghazi; Jawad, Aryan Xalis; Dawood, Shawnm Nasih (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objectives: A possible therapeutic effect of diagnostic tubal patency testing has been debated in the literature for more than half a century. The aim of this study was to evaluate the effect of flushing the fallopian tubes with water-soluble contrast medium during hysterosalpingography on subsequent pregnancy rates and to find out diagnostic findings of hysterosalpingography in infertile patients. Methods: A prospective study was conducted on 220 women. hysterosalpingography using water-soluble contrast media was done in a private clinic as part of their infertility work up from January 2012 to July 2012 in Erbil city, Kurdistan region, Iraq. The pregnancy rate was determined within six months from the procedure using water soluble contrast media and it was correlated with different hysterosalpingography findings. Results: The mean age (+SD) of the study population was 30.59 (+5) years. The clinical pregnancy rate was 23.2%. A statistically significant difference was found between the rate of pregnancy and hysterosalpingography results in which 27.2% of patients with normal hysterosalpingography and 6.8% of patients with abnormal hysterosalpingography got pregnant during six-month follow-up period after the procedure (P = 0.004). Conclusions: Flushing of the tubes with water-soluble contrast media during hysterosalpingography increases subsequent pregnancy rates in infertile patients.